2011 Eighth International Conference on Information Technology: New Generations 2011
DOI: 10.1109/itng.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Gap between Academia and Industry: The Case for Agile Methods in Thailand

Abstract: One of the recurring problems in information technology (IT) is a gap between education and industry. The gap takes several forms including difficulty in technology transfer, aligning research with the needs of practitioners, and preparing students to make the most effective contribution upon entering industry. This paper will examine the gap between education and industry, agile methods in the software sector, and computer science higher education in Thailand. We will summarize a new national initiative to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…This reliance on students for transferring technologies is, however, criticized by Hallinan and Paul who have concluded that the impact individual student can have is negligible. Several papers (eg, Chookittikul et al and Abercrombie) suggest the alignment of university curricula with industry to ensure relevancy. As a means for teaching complex methods, Michalik et al propose the use of technical drama a three‐step role play–based educational approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reliance on students for transferring technologies is, however, criticized by Hallinan and Paul who have concluded that the impact individual student can have is negligible. Several papers (eg, Chookittikul et al and Abercrombie) suggest the alignment of university curricula with industry to ensure relevancy. As a means for teaching complex methods, Michalik et al propose the use of technical drama a three‐step role play–based educational approach.…”
Section: Resultsmentioning
confidence: 99%
“…Fowler and Levine similarly present a model of a product's life cycle from its development to its decommissioning. A framework for technology transfer based on empirical research is presented by Shull et al Furthermore, several publications discuss the role education plays in software engineering technology transfer. Also, several publications report experiences from one or more software engineering technology transfer projects.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Chookittikul et al evaluated the increasing use of the agile techniques in software development companies in Thailand. The authors suggested that universities should create curricula that develop in their undergraduate students practical skills required by industry (mainly agile practices) to promote growth in local software businesses [6]. Sandberg et al report the use of Scrum in an industry-academia research consortium (involving ten industry partners and five universities in Sweden) [12].…”
Section: Related Workmentioning
confidence: 99%
“…In this context, studies illustrate a lack of alignment between what academia teaches and what the industry needs [Lethbridge et al 2007, Von Wangenheim & Silva 2009, Moreno et al 2012, Meira 2015, Barbosa et al 2020. However, promoting this connection is often lacking in university Computer Science programs and can severely hamper the growth of the software industry [Chookittikul et al 2011].…”
Section: Introductionmentioning
confidence: 99%
“…In response to these constant changes, agile methods represent a notable solution widely used nowadays [Kamei et al 2017]. The use of agile methods is a successful approach to developing software due to flexibility and low effort to maintain and emphasizes high quality and speed of development [Chookittikul et al 2011].…”
Section: Introductionmentioning
confidence: 99%